Joint-specific regulation of homeobox D10 expression in rheumatoid arthritis fibroblast-like synoviocytes. - Hyeonjeong Lee; Camilla R L Machado; Deepa Hammaker; Eunice Choi; Edward B Prideaux; Wei Wang; David L Boyle; Gary S Firestein (PLoS ONE, 2024)
Rheumatoid arthritis (RA) is a systemic immune-mediated disease characterized by joint inflammation and destruction. The disease typically affects small joints in the hands and feet, later progressing to involve larger joints such as the knees, shoulders, and hips. While the reasons for these joint-specific differences are unclear, distinct epigenetic patterns associated with joint location have been reported. In this study, we evaluated the unique epigenetic landscapes of fibroblast-like synoviocytes (FLS) from hip and knee synovium in RA patients, focusing on the expression and regulation of Homeobox (HOX) transcription factors. These highly conserved genes play a critical role in embryonic development and are known to maintain distinct expression patterns in various adult tissues. We found that several HOX genes, especially HOXD10, were differentially expressed in knee FLS compared with hip FLS. Epigenetic differences in chromatin accessibility and histone marks were observed in HOXD10 promoter between knee and hip FLS. Histone modification, particularly histone acetylation, was identified as an important regulator of HOXD10 expression. To understand the mechanism of differential HOXD10 expression, we inhibited histone deacetylases (HDACs) with small molecules and siRNA. We found that HDAC1 blockade or deficiency normalized the joint-specific HOXD10 expression patterns. These observations suggest that epigenetic differences, specifically histone acetylation related to increased HDAC1 expression, play a crucial role in joint-specific HOXD10 expression. Understanding these mechanisms could provide insights into the regional aspects of RA and potentially lead to therapeutic strategies targeting specific patterns of joint involvement during the course of disease.